Effect of third generation light emitting diode (LED) light curing units on the microleakage of composite restorative materials - Dumlao, Femerylle A.; Patalinghug, Ulysses C.; Medina III., Vicente O.; Yumul, Giselle S. (Adviser).
Failure of composite restorative materials has often been associated with marginal gap formation along the restoration-tooth interface due to inherent polymerization shrinkage of composite restorative materials. The degree of shrinkage could be influenced by several factors including the type of light curing unit (LCU) used to cure the composite. The aim of this study was to determine the effect of the type of light curing unit on the microleakage of composite materials. Seventy (70) freshly extracted bovine incisors with standardized Class V tooth preparations were used in the study. The composite restorative materials used were Filtek P90 and Ketac N100, while the LCUs used were a Prolux 570, SmartKite iQ and Radii Plus. The bovine incisors were a Prolux 570, SmartLite iQ and Radii Plus. The bovine incisors were randomly assigned to 6 groups of composite restorative materials and LCU combinations and one control group. The control group was filled with dental amalgam (positive control). The cavities were filled with the assigned restorative materials and stored in water for 24 hours. They were subjected to 500 cycles of thermal cycling using water baths of 5°C and 55° with a 60-second dwell time. The specimens were then immersed in 0.5% basic fuchsin at pH 4.0 for 24 hours. The teeth were sectioned and microleakage scoring was done using digital pictures of the specimens taken under 10X magnification. Data was analyzed using non-parametric Kruskal-Wallis test followed by a post-hoc test with a level of significance set at 0.05. Statistical analysis shows no significant difference in microleakage between the type of LCU used. Within the limitation of the study, the researches conclude that LED LCUs have no significant effect on the enamel and dentin microleakage scores of composite restorative materials.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental materials; Light emitting diode (LED).